PENINGKATAN DISIPLIN KERJA PEGAWAI MELALUI MOTIVASI - Utin Wahyu Rukmana Dewi E.01108010 (FISIP Universitas Tanjungpura, 2013)
Discipline became a necessity in performing the task, but in fact there are still employees who are late for work and the lack of opportunities in doing promotion employee. In this case the researcher uses descriptive method because the researcher will describe the condition or description of the object to be studied. In doing study is expected to achieve the goal of increasing employee discipline in carrying out the tasks assigned by the motivation given leader. Of the study results in a lack of motivation get given leadership to the district office employees. The advice from researchers that where district leaders melakuakan approach to subordinates by monitoring each room to find out what the difficulty of the employee in performing a given task.Keywords : ekstrinsik motivation, working condition, working status, organization policy, quality of relationship.